(untitled) (CIPEEX, 2022)
THIS WORK AIMS TO ANALYZE FEELINGS AS A MANIFESTATION OF THE VIROCENE THROUGH THE POST-APOCALYPTIC FANTASY AND SCIENCE FICTION SERIES SWEET TOOTH (2021-ATUAL) FROM THE STREAMING CHANNEL NETFLIX. IT DISCUSSED HERE HOW THE H5G9 VIRUS AND ITS IMPACT ON THE REPRODUCTION AND MAINTENANCE OF HUMAN LIFE, ETHICS, POLITICS AND THE ENVIRONMENT MANIFEST IN THE EMERGENCE OF FEELINGS OF ANXIETY, LOVE, HATE, AND REMORSE, AMONG OTHERS, THAT STRUCTURE THE VIROCENE PHENOMENON. IN THIS PERIOD OF PANDEMIC AND POST-PANDEMIC COVID-19, VIROCENE REVEALED ITSELF TO BELONG TO THE CONTEMPORARY ERA AS A SUPERPOSITION OF THE ANTHROPOCENE. ON THE ONE HAND, THE ANTHROPOCENE IS NOTABLE FOR ACTIVATING ACTIONS AGAINST HUMANITY AND THE ENVIRONMENT WITH A LONG-LASTING IMPACT OF ANTHROPOGENIC DESTRUCTIBILITY. ON THE OTHER HAND, THE VIROCENE TRANSCENDS THESE SAME IMPACTS, SUPPORTED BY POWER STRUCTURES THAT TRIGGER IMPONDERABLE, FLEETING AND DANGEROUS PHENOMENA. THESE PHENOMENA PRESENT THEMSELVES IN A MANIFESTO OF FAVOURITISM TO CAPITALISM, HIGHLIGHTING BIOPOLITICS UNDER A SOCIAL CONTROL OF VULNERABILITIES IN A STRATEGY MEDIA TO POWER RELATIONS. THIS RESEARCH’S OBJECTIVE WILL ANALYZE ISSUES THAT PERMEATE GENDER, RACE, SCIENCE AND THE ENVIRONMENT IN WORLDS THAT DISREGARD THE HUMAN AND ENVIRONMENTAL VULNERABILITIES THAT HAVE SPREAD IN THE VIROCENE ERA. FOR THIS, A STREAMING SERIES OF THE FANTASY AND SCIENCE FICTION GENRES ARE USED THAT, ALTHOUGH THEY AIM AT ENTERTAINMENT, ADMITTEDLY SPECULATE ON POSSIBLE FUTURES AND ALTERNATIVE ONTOLOGIES AND POSITION THEMSELVES IN THE SOCIAL ARENA WHILE ALSO BEING ANCHORED IN CONTEMPORARY ANXIETIES, FEARS AND DEBATES. IN THIS SENSE, IT WILL EXAMINE WHICH NUANCE BETWEEN THE INCLINATION OF EMOTION AND THE EMOTIONAL UPHEAVALS SURROUNDING THE SERIES’ EIGHT EPISODES IS PERCEPTIBLE. THIS NUANCE IS INTEGRATED WITH THE VERACITY AND LINKED TO THE FACTS OF A HUMAN-DEER HYBRID CHILD SEPARATED FROM SOCIETY, EAGER TO DISCOVER WHAT IS BEYOND THE FENCES THAT ISOLATED HIM FROM THE WORLD. IT IS, THEREFORE, AN ANALYSIS IN SYNERGY WITH THE POST-PANDEMIC WORLD IN WHICH EVERYTHING SEEMS TO BE A CONTRADICTION OF CONSCIENCES, FOUNDATIONS AND HUMAN EXPERIENCES SUBSIDIZED BY REDEFINITIONS AND REFLECTIONS ON LIFE ON EARTH, WHICH IS ONE OF THE SEVENTEEN OBJECTIVES OF SUSTAINABLE DEVELOPMENT AT THE UN. THE PRELIMINARY RESULT OF THIS RESEARCH INDICATES THAT MUCH MORE THAN CONCEPTS, IDEAS, INTENTIONS AND REPRESENTATIONS, THE FEELINGS EMERGING IN CIRCUMSTANCES OF EPIDEMICS AND PANDEMICS STRUCTURE THE EVENTS IN THE VIROCENE. VIROCENE CONSTITUTES THE DIMENSION OF ENCOUNTERS AND UNCERTAINTY THAT FACE THE VIRUS AS A THING-POWER THAT DESTABILIZES AND RECONFIGURES THE RELATIONSHIPS OF TIME, SPACE AND POWER.